2017
DOI: 10.3390/su9071039
|View full text |Cite
|
Sign up to set email alerts
|

More Than a Potential Hazard—Approaching Risks from a Social-Ecological Perspective

Abstract: Risks have been classically understood as a probability of damage or a potential hazard resulting in appropriate management strategies. However, research on environmental issues such as pollutants in the aquatic environment or the impacts of climate change have shown that classical management approaches do not sufficiently cover these interactions between society and nature. There have been several attempts to develop interdisciplinary approaches to risk that include natural as well as social science contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Völker et al . 26 found that “92.8% of media articles imply that risk of microplastics exist and harmful consequences are highly probable” (p.7) 40 . However, in this specific case the evidence provided to date suggests that the chemicals related to plastics in microplastics exert a negligible effect on human health despite commonly being stated in the press, and also in the scientific literature 5 , 15 , 26 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Völker et al . 26 found that “92.8% of media articles imply that risk of microplastics exist and harmful consequences are highly probable” (p.7) 40 . However, in this specific case the evidence provided to date suggests that the chemicals related to plastics in microplastics exert a negligible effect on human health despite commonly being stated in the press, and also in the scientific literature 5 , 15 , 26 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The sources to microplastics in aquatic ecosystems are mainly land-based and are usually divided into primary sources (emissions of micro-sized polymeric particles) and secondary sources (larger sized polymer items that are broken down in the environment to microplastics) [10]. The abrasion of synthetic textiles leads to shedding due to mechanical stress of the textile fibres and takes place both during production [12] and use e.g., washing and drying procedures [14].…”
Section: Textiles As a Source To Microplasticsmentioning
confidence: 99%
“…Environmental monitoring shows that microplastics are present in aquatic environments at a growing rate [8,9]. At the same time, there is an uncertainty to how large the risks are that microplastics pose, and there is currently no studies available that can provide evidence that the micro-sized plastic particles pose any hazard in itself [10,11]. However, for emissions to air and consequent inhalation in the human lung, the potential hazard related to size and shape especially related to emissions in working environment is discussed [12].…”
Section: Introductionmentioning
confidence: 99%
“…For Kermisch (2012), the concepts of risk and responsibility are increasingly intertwined, a tendency that has grown by increasing public awareness, and suggested that a form of virtue-responsibility should be integrated in the concept of risk. Ondeed, risk has a polysemic nature, whose objective and subjective dimensions must be understood as complementary, considering the technical and social components, being socially, culturally and mentally constructed (Covello & Mumpower, 1985;Hansson, 2010;Völker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%